Total factor productivity growth when factors of production generate environmental externalities - Anastasios Xepapadeas; Dimitra Vouvaki (Fondazione Eni Enrico Mattei (FEEM), 2009)
Total factor productivity growth (TFPG) has been traditionally associated with technological change. We show that when a factor of production, such as energy, generates an environmental externality in the form of CO2 emissions which is not internalized because of lack of environmental policy, then TFPG estimates could be biased. This is because the contribution of environment as a factor of production is not accounted for in the growth accounting framework. Empirical estimates confirm this hypothesis and suggest that part of what is regarded as technology's contribution to growth could be attributed to the use of environment in output production.
Keywords: O47; Q20; Q43; 330; Total Factor Productivity; Sources of Growth; Environmental Externalities; Energy; Environmental Policy